Improving the Effectiveness of School Counselling: Consensus, Collaboration, and Clinical Supervision - Walker, Karen (Canadian Journal of Counselling and Psychotherapy, 2015)
In this literature review, factors influencing the effectiveness of the services and programs provided by school counsellors are examined. Specific influences reviewed were professional identity, collaborative working practices, and clinical supervision. Analysis revealed that the principles of egalitarianism, relationship, and connectedness permeate everything that school counsellors do, and that collaborative working practices, clinical supervision, and the concept of professional identity are inextricably linked. Implications for practice are discussed and recommendations for future research are provided. Researchers are challenged to address the dearth of literature on Canadian school counselling practices.